THE SCIENCE OF LAW REGARDING NEW LEGAL CONTRACTUAL COMMERCIAL INSTITUTIONS FROM THE POINT OF VIEW OF THE CONTINENTAL CIVIL LAW SYSTEMS: THE SPANISH AND GERMAN EXAMPLES - Palao-Uceda, Juan (Review of European and Comparative Law, 2018)
This article tries to return to the essence of civil law which, with a little more than ten key contractual institutions, allows all disputes created from newly founded institutions to be examined and interpreted. If law is science it must be able to be reduced to a set of basic concepts that have been coined and concluded from daily contractual practice and, almost in their entirety, have been in force over time. Hence the study of Roman law and Roman legal tradition remain a constant reference to our continental law. However, this does not prevent them from being open to gradual enrichment.